From Far West to East: Joining the Molecular Architecture of Imidazole-like Ligands in HO-1 Complexes - Giuseppe Floresta; Antonino Nicolò Fallica; Vincenzo Patamia; Valeria Sorrenti; Khaled Greish; Antonio Rescifina; Valeria Pittalà (MDPI AG, 2021)
HO-1 overexpression has been reported in several cases/types of human malignancies. Unfortunately, poor clinical outcomes are reported in most of these cases, and the inhibition of HO-1 is considered a valuable and proven anticancer approach. To identify novel hit compounds suitable as HO-1 inhibitors, we report here a fragment-based approach where ligand joining experiments were used. The two most important parts of the classical structure of the HO-1 inhibitors were used as a starting point, and 1000 novel compounds were generated and then virtually evaluated by structure and ligand-based approaches. The joining experiments led us to a novel series of indole-based compounds. A synthetic pathway for eight selected molecules was designed, and the compounds were synthesized. The biological activity revealed that some molecules reach the micromolar activity, whereas molecule 4d inhibits the HO-1 with an IC50 of 1.03 μM. This study suggested that our joining approach was successful, and a novel hit compound was generated. These results are ongoing for further development.